Modulating the gut-immune axis to alleviate rheumatoid arthritis: mechanistic insights and therapeutic potential of traditional Chinese medicine - Zhan, Jiaguo; Fu, Yu; Liu, Zhanbiao; Zhang, Shaozhuo; Wu, Chongming (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA), a chronic autoimmune disorder marked by systemic inflammation and joint destruction, remains challenging to treat due to the limitations of conventional therapies, including side effects and diminishing efficacy. Emerging research underscores the gut-immune axis—a dynamic interplay between gut microbiota, immune responses, and inflammation—as a pivotal contributor to RA pathogenesis. Traditional Chinese Medicine (TCM), recognized for its established safety and accessibility, has been shown to synergistically alleviate symptoms of RA when used alongside conventional treatments, while significantly reducing drug-related toxicity. Pre-clinical models and clinical trials have demonstrated that TCM formulations, bioactive phytochemicals, and their metabolites can modulate the gut-immune axis by restoring gut microbiota balance and regulating immune-inflammatory pathways. This review summarizes the multi-target effects of TCM, including microbiota modulation and immune system regulation, and proposes a microbiota-centered therapeutic strategy for RA. Although the role of Traditional Chinese Medicine in regulating gut microbiota and immune modulation supports its clinical translatability, rigorous mechanistic studies remain essential to facilitate its integration into mainstream rheumatology treatment strategies. This involves research on its pharmacokinetic-pharmacodynamic characteristics, validation of microbiome-dependent mechanisms, and investigation into mechanisms involving microbial metabolites. By integrating millennia of empirical knowledge with cutting-edge systems biology, TCM presents a microbiota-centered holistic strategy for RA management.